Limestone Acoustic Emission Evolution Characteristics Under Different Experimental Loading and Unloading Conditions - Li, Jielin; Hong, Liu; Zhou, Keping; Xia, Caichu; Zhu, Longyin (Frontiers in Physics, 2020)
To study the acoustic emission evolution characteristics of saturated limestone under different loading and unloading paths, three cyclic loading and unloading tests were conducted with different loading rates and initial cyclic peak stresses, and acoustic emission monitoring was performed simultaneously. The results indicate that, during loading and unloading, the intermediate-frequency signals of saturated rock exhibit a variation trend of sparse–dense–sparse signals, whereas the low-frequency signals are continuously and massively produced. With the increase in the loading rate, the development trends of cumulative hits and energy become closer, and the development form of ringing count changes from N-type to U-type and then to N-type. The slight increase period and attenuation period are extended, whereas the intense growth period and postpeak calm period are shortened. With an increase in the initial cyclic peak stress, the change in cumulative energy is more obvious than that in cumulative hits near the rock failure. The development form of the ringing count changes from U-type to W-type and then to N-type, and each period is first shortened and then extended. With the increase in loading rate, the increase in the slow-change period tends to change from gradually increasing to increasing and then decreasing. By contrast, the increase in the step tends to change to a gradual increase. With the increase in the initial cyclic peak stress, the duration of and increase in the energy in the step and the slow-change period tend to decrease and then increase.